Hydrogen spillover effect enhanced by carbon quantum dots activated MoS2. (31st October 2022) - Song, Lili; Zhang, Xiaoyun; Zhu, Shifan; Xu, Yixue; Wang, Yuqiao
Abstract: The weak hydrogen adsorption and slow catalytic kinetics are unfavorable for MoS2 as a catalyst for hydrogen evolution reaction (HER) in alkaline solution. Herein, carbon quantum dots (CQDs) with high proton adsorption energy were expected to enhance the proton adsorption of MoS2 during the HER process. The CQDs activated MoS2 can establish a suitable hydrogen adsorption gradient due to the surface charge redistribution to promote the hydrogen spillover pathway. After the CQDs were loaded on MoS2, the charge distribution would gradually transfer from the C sites of CQDs to the S sites on MoS2 surface, showing a charge gradient distribution calculated by density functional theory predictions. The adsorbed hydrogen can spill over from hydrogen-enriched CQDs to hydrogen-deficient MoS2 in HER. The process could be monitored by the quasi in-situ electrochemical impedance spectroscopy. The enhanced hydrogen spillover effect by CQDs activated MoS2 can pave the way for the design and preparation of efficient and low-cost catalysts. Graphical abstract: Image 1 Highlights: The hydrogen spillover effect was induced by the introduction of proton-collection CQDs. The induced hydrogen spillover pathway can be attributed to the gradient charge distribution. Surface charge redistribution was estimated by differential charge density and XPS analysis. Hydrogen spillover pathway was described by DFT calculations and quasi in-situ EIS techniques.